1983
DOI: 10.1099/00207713-33-1-26
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Study of Paracoccus denitrificans

Abstract: Isolates of Paracoccus denitrijicans were obtained from various habitats by enrichment in a mineral medium, using molecular hydrogen as the hydrogen donor and nitrate as the hydrogen acceptor. A total of 11 strains were compared with the following three reference strains: P . denitrijcans Stanier 381T (type strain) (= DSM 65T = ATCC 17741T), Morris (= DSM 413 = ATCC 19367), and Vogt (= DSM 415). A computer analysis based on 235 characters indicated that the strains clustered into subgroups. Deoxyribonucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
142
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(147 citation statements)
references
References 27 publications
5
142
0
Order By: Relevance
“…This finding is in agreement with taxonomic studies that showed that DSM413 and DSM415 are closely related and that DSM65 T is a rather distinct member of the Paracoccus genus (17). An interesting result came from a comparison of the fingerprints of DSM413 and NCIB8944.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in agreement with taxonomic studies that showed that DSM413 and DSM415 are closely related and that DSM65 T is a rather distinct member of the Paracoccus genus (17). An interesting result came from a comparison of the fingerprints of DSM413 and NCIB8944.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of antibiotics on cell growth was assessed after 3 days at 25 8C. A strain was considered susceptible when the diameter of the inhibition zone was .13 mm, intermediate at 10-12 mm and resistant at ,10 mm as described by Nokhal & Schlegel (1983).…”
Section: Mucilaginibacter Rigui Wpcb133 T (Eu747841)mentioning
confidence: 99%
“…Susceptibility to antibiotics was determined by the disc diffusion method using filter-paper discs (Beijing Pharmaceutical Company), which contained various antibiotics as specified below. Growth inhibition effects were observed and estimated according to Nokhal & Schlegel (1983) after incubation on MA (pH 7.5) for 2 days at 30 8C. The inhibition zones were measured from the edges of susceptibility disks to the edges of the clear zones.…”
mentioning
confidence: 99%